ANALISIS PENGEMBANGAN INDUSTRI KECIL KERAJINAN GENTENG DALAM UPAYA MENINGKATKAN KESEJAHTERAAN PENGRAJIN: (Studi Pada Masyarakat Desa Wringinanom Kecamatan Sambit Kabupaten Ponorogo) - Dodik Cahyono (Universitas Darul Ulum, 2021)
Small tile craft industry is a folk craft that needs to be developed and preserved. Small industry problems do not only lie in capital, materials, weather and support from human resources. The aim of this research is to find out the development and how the views of Islamic Economics regarding the development of the tile industry in an effort to improve the welfare of craftsmen in Wringinanom Village. The type of this research is field research. Data sources consist of data sources and secondary data sources. The population of this study consisted of all tile craftsmen in Wringinanom Village, Sambit District, Ponorogo Regency totaling 39 craftsmen with a sample of 25 percent. The data collection techniques were observation, interviews and. Data analysis was carried out by Data Reduction, Data Presentation, Conclusion Drawing and Verification. The results showed that the welfare of tile craftsmen in Wringinanom village was increasing, in general the tile entrepreneurs in Wringinanom Village did not use loans, the demand for roof tiles in Wringinanom village seasonal nature, tile craftsmen in Wringinanom village can absorb labor for the surrounding community.